2012
DOI: 10.1016/j.ijms.2012.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Rapid lipid profiling of bacteria by online MALDI-TOF mass spectrometry

Abstract: a b s t r a c tThe rapid identification of bacteria is of increasing interest in food, biosafety, and clinical analysis. In this paper, we report a technique for rapid lipid profiling of bacteria by online droplet-deposited MALDI mass spectrometry. In the experiment, lipids in bacterial cells (Escherichia coli, Salmonella, and Bacillus subtilis) are extracted with the mixture of chloroform/methanol via ultrasonication. The extracts are nebulized into suspended droplets and then instantly analyzed with an onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Lipids were extracted from Bacillus and Brevibacillus using chloroform/methanol (2:1) since this method was used previously with successful outcomes [ 10 , 12 , 44 ]. The MALDI-TOF-MS spectra of lipids extracted from all seven species— B. amyloliquefaciens B0177, B. cereus B0002, Br.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipids were extracted from Bacillus and Brevibacillus using chloroform/methanol (2:1) since this method was used previously with successful outcomes [ 10 , 12 , 44 ]. The MALDI-TOF-MS spectra of lipids extracted from all seven species— B. amyloliquefaciens B0177, B. cereus B0002, Br.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have confirmed that phosphatidylethanolamine (PE) and phosphatidylglycerol (PG) are the most abundant phospholipids in bacteria such as Bacillus spp. [ 44 , 46 , 47 ] and Escherichia coli [ 44 ]. Bacillus has also been reported to produce other categories of lipids such as digalactosyldiacylglycerol (DGDG) [ 11 , 44 ], phosphatidylcholine (PC) [ 11 , 44 , 48 ] and fatty acids [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of thermal processing [66] LC-TOF Analysis of pesticides in fruits and vegetables [67] GC-TOF Quantitative analysis of acetaldehyde in foods consumed [68] LC-TOF Screening natural antioxidants in peanut shell [69] UHPLC-TOF Hexabromocyclododecane diastereomers [70] Type Application References UHPLC-TOF 19 antibiotics in dairy products [71] MALDI-TOF Microscale strategy to detect spermine and spermidine in food [72] LC-TOF Determination of phthalates in edible salts from food markets in Korea [73] LC-QqTOF Simultaneous determination five major antioxidant compounds [74] MALDI-TOF Monitoring of she-donkey's milk contamination or adulteration [75] MALDI-TOF Quantitating curcumin in food condiments and dietary supplements and screening of acrylamide-induced ROS protein indicators [76] LC-QqTOF Quantitating curcumin in food condiments and dietary supplements and screening of acrylamide-induced ROS protein indicators [45] UHPLC-TOF Analysis of illicit dietary supplements sold in the Italian market: Identification of a sildenafil thioderivative as adulterant [46] LC-TOF Simultaneous investigation of sesquiterpenes, pyrrolizidine alkaloids, and N-oxides in butterbur (Petasites hybridus) [77] UHPLC-QqTOF Determination of 141 pesticides in tea [78] UHPLC-QqTOF Determination of tadalafil and N-desmethylsibutramine in health and dietary supplements [79] LC-QqTOF Seven fluorescent whitening agents in food contact paper package materials [80] Lipidomics GC × GC-TOF Unsaponifiable fraction of lipids belonging to various types of milk [22] UHPLC-QqTOF Rapid and highly accurate detection of steryl glycoside [81] MALDI-TOF Rapid lipid profiling of bacteria [82] MALDI-TOF Detection of glycated phospholipids in heattreated food samples [83] …”
Section: Target Analysismentioning
confidence: 99%
“…Demands for rapid and reliable identification of pathogens have brought a number of alternatives to the classical MALDI‐TOF MS protein profiling sample preparation protocols . Identification can be also accomplished by the profiling of bacterial lipids using an online droplet‐deposited MALDI‐TOF MS, as shown with Escherichia coli , Salmonella , and Bacillus subtilis . Extensive and advanced computational analysis may also contribute to improvements in the discriminatory power of the method.…”
mentioning
confidence: 99%